Torticollis - Agusnadi M.; Sjabaroeddin Loebis (Indonesian Pediatric Society, 1995)
We report a case of 12 years old girl with acquired torticollis caused by juvenile rheumatoid arthritis. The main complaint are the head inclined to the right and the pain of right neck. We established the working diagnosis based on the history and typical clinical pictures. After having physiotherapy and drug therapy with acetosal, the patient become beter with the head and neck is in normal condition again. The importance is to treat cases of tortocollis as soon as possible, before there is a contractire of the muscles of the neck.